Determinants of agricultural land prices in Ostrobothnia Finland : a hedonic pricing approach - Dahlvik, Mikael (SLU/Dept. of Economics, 2017)
The objective of this thesis was to examine the determinants of parcel prices in Ostrobothnia, Finland. A hedonic pricing model was used to analyse 147 transactions over the years 2013, 2014 and 2015. The model consisted of 14 explanatory variables, categorized into structural and natural attributes. The results indicate that the structural variables, e.g. the size of the cropland, has a nonlinear relationship with the per hectre price of parcels. Specifically, price per hectare increases up to 9 hectares and then it begins to decline. The results also show that an increase in the distance from areas of trade lowers the price by 1% per kilometre. Furthermore, the results suggest that farm sizes in each municipality has a positive effect on the parcel prices. With respect to natural attributes, e.g. soil quality and geographical location, the estimated results reveal that the organic soils are 79.3% and moraine soils are 36.4% lower priced than fine-grained soils. The geographical results indicate a 19.9% higher price in the southern part of Ostrobothnia, compared to the middle part.